Evaluation of the Effect of Functional Contouring of the Palatal Vault of Maxillary Complete Denture on Clarity of Speech Sounds in Edentulous Patients: An In Vivo Study - Sonal Jain; Manimegalai; Bhavin Purohit; Reshma Amin; R Arun; Deepika R Pai (Journal of Pharmacy and Bioallied Sciences)
Background: The articulatory system, which consists of the tongue, lips, teeth, hard palate, and soft palate, is a component of phonetics, the study of speech sounds. Speech sounds are negatively impacted by the lack of teeth and surrounding tissues in edentulous people. Phonetics has not gotten the same level of attention as denture mechanics and aesthetics, despite notable developments in these areas. The purpose of this research is to increase speech clarity in edentulous individuals by contouring the palatal vault of maxillary full dentures. Materials and Methods: Sixty edentulous individuals, who spoke Tamil or English well and were between the ages of 45 and 75, were chosen. Speech sounds from each individual were captured both before and after the maxillary full dentures’ palatal vault was functionally contoured using visible light cure acrylic resin. For a quantitative evaluation, spectrograms were used to examine the speech samples. Results: For most patients, functional contouring of the palatal vault markedly enhanced speech sound quality. The spectrogram analysis’s arbitrary results showed that most participants’ voice clarity had improved by 30% and that the time it took patients to attain clear speech after having a denture had been significantly reduced. Conclusion: The research comes to the conclusion that edentulous patients’ speech clarity is improved by functionally contouring the palatal vault using visible light cure acrylic resin in maxillary full dentures. By using this technique, patients are more satisfied with their dentures and the adaption time is shortened.